Effect of the screw type (S2-alar-iliac and iliac), screw length, and screw head angle on the risk of screw and adjacent bone failures after a spinopelvic fixation technique: A finite element analysis - Shin, Jong Ki (PLoS One, 2018)
PURPOSE: Spinopelvic fixations involving the S2-alar-iliac (S2AI) and iliac screws are commonly used in various spinal fusion surgeries. This study aimed to compare the biomechanical characteristics, specifically the risk of screw and adjacent bone failures of S2AI screw fixation with those of iliac screw fixation using a finite element analysis (FEA). METHODS: A three-dimensional finite element (FE) model of a healthy spinopelvis was generated. The pedicle screws were placed on the L3-S1 with three different lengths of the S2AI and iliac screws (60 mm, 75 mm, and 90 mm). In particular, two types of the S2AI screw, 15°- and 30°-angled polyaxial screw, were adopted. Physiological loads, such as a combination of compression, torsion, and flexion/extension loads, were applied to the spinopelvic FE model, and the stress distribution as well as the maximum von Mises equivalent stress values were calculated. RESULTS: For the iliac screw, the highest stress on the screw was observed with the 75-mm screw, rather than the 60-mm screw. The bones around the iliac screw indicated that the maximum equivalent stress decreased as the screw length increased. For the S2AI screw, the lowest stress was observed in the 90-mm screw length with a 30° head angle. The bones around the S2AI screw indicated that the lowest stress was observed in the 90-mm screw length and a 15° head angle. CONCLUSIONS: It was found that the S2AI screw, rather than the iliac screw, reduced the risk of implant failure for the spinopelvic fixation technique, and the 90-mm screw length with a 15° head angle for the S2AI screw could be biomechanically advantageous.